2002
DOI: 10.1046/j.1439-0531.2002.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Semen Characteristics and Plasma Levels of Testosterone after Bilateral Vasectomy in Bucks

Abstract: The effects of bilateral vasectomy on the seminal characteristics were assessed in six bucks of the Canarian breed. In addition, we tried to establish the effects of vasectomy on the plasmatic concentrations of testosterone and the libido of the bucks. Semen samples were collected once a week from 8 weeks before to 16 weeks after vasectomy; blood samples were collected prior to vasectomy, and then at once and 1 week after vasectomy and every 2 weeks from the week 4 to the end of the experiment. One week after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
4
3
0
Order By: Relevance
“…In group I, no significant change (P > 0.05) in testosterone was observed at different postoperative time intervals. It was attributed to bilateral vasectomy, which does not exert a remarkable effect on the steroidogenic functionality of the testicle as also reported by Batista et al (24). In group II, a significant decrease (P < 0.01) in plasma testosterone was observed immediately after the operation up to the 7th postoperative day.…”
Section: Discussionsupporting
confidence: 69%
“…In group I, no significant change (P > 0.05) in testosterone was observed at different postoperative time intervals. It was attributed to bilateral vasectomy, which does not exert a remarkable effect on the steroidogenic functionality of the testicle as also reported by Batista et al (24). In group II, a significant decrease (P < 0.01) in plasma testosterone was observed immediately after the operation up to the 7th postoperative day.…”
Section: Discussionsupporting
confidence: 69%
“…In group I, no significant change (p > 0.05) in testosterone was observed at different postoperative time intervals. It might be attributed to bilateral vasectomy which do not exert remarkable effect on steroidogenic functionality of the testicle as also reported by Batista et al 38 Whereas, in group II, a significant decrease (p < 0.01) in plasma testosterone was observed immediately after operation up to 7th postoperative day. It might be due to the reduction of testicular blood flow and loss of testicular interstitial tissue.…”
Section: Hormonal Estimationsupporting
confidence: 73%
“…In other studies, it has been shown that bilateral vasectomy does not strongly affect the endocrine function of the testis over time [36] although it may result in damage to spermatogenesis in vasectomized rats [37]. …”
Section: Discussionmentioning
confidence: 99%